Sequences of the Escherichia coli dnaG primase gene and regulation of its expression. - Smiley, B L (1982)
The nucleotide sequence of a cloned section of the Escherichia coli chromosome containing the dnaG primase gene [Lupski, J., Smiley, B., Blattner, F. & Godson, G. N. (1982) Mol. Gen, Genet. 185, 120--128] has been determined. The region coding for the dnaG primase has been identified by NH2-terminal and tryptic peptide amino acid analysis of the dnaG protein. The coding region is 1,740 base pairs long (580 amino acids) and is preceded by an unusual ribosome-binding site sequence (G-G-G-G). The dnaG gene is read in the same direction as the adjacent rpoD gene, but no obvious promoter sequences can be found for either gene within several hundred nucleotides upstream. Other unusual features of the dnaG gene that may explain the maintenance of its product at low copy number are the presence of a RNA polymerase terminator 31 nucleotides upstream from the ATG initiator codon and greater use (3--10 times) of certain condons that occur infrequently in other E. coli genes. The nucleotide sequence has also been correlated with data from transposon Tn5 insertional inactivation mapping.